Pengaruh Keterlibatan Kerja dan Gaya Kepemimpinan Transformasional Terhadap Kinerja Pegawai Dimediasi Kepuasan Kerja pada Kementerian Agrarian dan Tata Ruang/Pertahanan Nasional - Apriliana Ramadhani; Ida Aryani; Neuneung Ratna Hayati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the influence of work engagement and transformational leadership style on employee performance through job satisfaction at the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN). The research problem is motivated by the importance of improving employee performance in supporting bureaucratic reform and improving the quality of public services, amidst the challenges of complex vertical organizations and increasing demands for public services. This study uses a quantitative approach with a causality design. Primary data were collected by distributing questionnaires to 220 State Civil Apparatus (ASN) selected using a cluster random sampling technique based on the rule of thumb (Hair et al., 2017). The research instrument used a 5-point Likert scale to measure the variables of work engagement (Schaufeli & Bakker), transformational leadership style (Bass & Avolio), job satisfaction (Herzberg), and employee performance (Bernardin & Russell). The data analysis technique used Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the help of SmartPLS. The results of the study indicate that job engagement has a positive effect on job satisfaction, leadership style has a positive effect on job satisfaction, and job satisfaction has a positive effect on employee performance. Mediation testing through bootstrapping procedures shows that job satisfaction mediates the influence of job engagement and leadership style on employee performance. This finding confirms that improving employee performance in the ATR/BPN environment is not only directly influenced by organizational behavioral factors, but also through increasing job satisfaction as an intervening variable. The conclusion of this study states that strengthening job engagement and implementing an effective transformational leadership style are important strategies for improving job satisfaction and employee performance sustainably in the public sector.to improve job satisfaction and sustainable employee performance in the public sector.